Content Marketing Strategy and Development - Darvidou, Konstantia (Technium Business and Management, 2024)
This document outlines a comprehensive content marketing strategy aimed at driving audience engagement, loyalty, and business growth. It emphasizes a strategic approach to content planning, creation, distribution, and performance measurement, all centered around understanding and meeting audience needs. Key components include audience research, persona development, content audits, and gap analysis to ensure content relevance and alignment with market trends. Additionally, the strategy covers effective content creation processes, multi-channel distribution plans, and promotional tactics, leveraging both organic and paid methods to amplify reach. Content personalization and repurposing are discussed as methods to enhance engagement and extend content lifespan. The document concludes with best practices for tracking and optimizing content performance, highlighting the importance of agility and continuous improvement in a successful content marketing strategy.